1988
DOI: 10.1002/j.1460-2075.1988.tb03183.x
|View full text |Cite
|
Sign up to set email alerts
|

Two proteins crosslinked to RNA containing the adenovirus L3 poly(A) site require the AAUAAA sequence for binding.

Abstract: The major proteins crosslinked by UV light to RNA containing the adenovirus‐2 L3 poly(A) site are species of 155, 68 and 38 kd mol. wt (p155, p68 and p38). Mutation of AAUAAA to AAGAAA prevented cross‐linking of the two larger proteins and destroyed the ability of the RNA to compete for binding of these proteins. However, association of p155 and p68 with precursor was unaffected by deletion of sequences downstream of the poly(A) site critical for in vitro polyadenylation. These two proteins are in the polyaden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
91
0

Year Published

1991
1991
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(100 citation statements)
references
References 61 publications
9
91
0
Order By: Relevance
“…Deletion of nucleotides beyond the cleavage site reduces the ability of CPSF-160 to bind to the PAS. Mutations of the PAS abolished the cross-linking of nuclear extract [89], while they only have a small effect on the cross-linking of the recombinant CPSF-160 [88], suggesting that other proteins are required for the highly specific binding to the PAS by CPSF-160. CPSF-160 can also bind at a site other than the PAS in HIV pre-mRNA [90].…”
Section: Cpsf-160 (Cft1p/yhh1p)mentioning
confidence: 99%
“…Deletion of nucleotides beyond the cleavage site reduces the ability of CPSF-160 to bind to the PAS. Mutations of the PAS abolished the cross-linking of nuclear extract [89], while they only have a small effect on the cross-linking of the recombinant CPSF-160 [88], suggesting that other proteins are required for the highly specific binding to the PAS by CPSF-160. CPSF-160 can also bind at a site other than the PAS in HIV pre-mRNA [90].…”
Section: Cpsf-160 (Cft1p/yhh1p)mentioning
confidence: 99%
“…Alternatively, it may be the subunit in contact with the cleavage site, or it may interact with both sites. The first possibility would be reminiscent of early studies which showed that the binding of the p64 subunit of mammalian CstF was dependent on the AAUAAA sequence (37,38).…”
Section: Table Imentioning
confidence: 99%
“…While examining these differences, we discovered CstF-64 (8), which is a paralog of the 64,000 M r subunit of the cleavage stimulation factor (CstF-64) (9)(10)(11). CstF-64 is expressed in nuclei of early spermatogenic cells (5,12).…”
mentioning
confidence: 99%